Implementasi Human Relations Pattaya Steamboat Yakiniku melalui Program Achievement Motivation - Andini Rahmania Nurhakim; Ani Yuningsih (Bandung Conference Series: Public Relations, 2021)
Abstract. This research aims to find out and review the increasing motivation of outstanding employees who are focused on human relations activities between employees within the scope of the company that is given more attention to foster work motivation the key to human relations activity is motivation. Pattaya Steamboat Yakiniku (PSY) through achievment motivation activities.Achievment motivation is tied to this study using the motivation theory approach put forward by McClelland.This theory provides a brief explanation of how individual behavior in employee work activities can be reviewed from various aspects that contribute to the emergence of such behavior, causal factors, and things that can foster motivation.Both personality and motivation of achievement are measured using interview methods, observation and down directly into the field.The subjects of the study were three people, who were Finance and Communication Bussines Manager Pattaya Steamboat Yakiniku (PSY) as well as two employees of Pattaya Steamboat Yakiniku (PSY).So that the continuity of the outstanding motivation program can run well because Pattaya Steamboat Yakiniku (PSY) has had the knowledge and various ways to maintain the work motivation of its employees to continue to increase and the employees who participate in the implementation of the motivation program continues to be motivated. Abstrak. Penelitian ini bertujuan untuk mengetahui dan mengkaji peningkatan motivasi berprestasi karyawan yang difokuskan pada kegiatan human relations antar pegawai dalam ruang lingkup perusahaan yang diberikan perhatian lebih untuk menumbuhkan motivasi kerja. Kunci aktivitas human relations adalah motivasi. Pattaya Steamboat Yakiniku (PSY) melalui kegiatan achievement motivation. Motivasi berprestasi atau achievment motivation terikat pada penelitian ini menggunakan pendekatan teori motivasi yang dikemukakan oleh McClelland. Teori ini memberikan penjelasan singkat bagaimana prilaku individu dalam aktivitas kerja karyawan dapat ditinjau dari berbagai aspek yang melatari munculnya prilaku tersebut, faktor penyebab, serta hal-hal yang dapat menumbuhkan motivasi. Baik kepribadian maupun motivasi berprestasi diukur menggunakan metode wawancara, observasi dan turun langsung ke lapangan. Subyek penelitian berjumlah tiga orang, yang merupakan Finance and Communication Bussines Manager Pattaya Steamboat Yakiniku (PSY) serta dua karyawan Pattaya Steamboat Yakiniku (PSY). Sehingga keberlangsungan program motivasi berprestasi tersebut dapat berjalan dengan baik karna pihak Pattaya Steamboat Yakiniku (PSY) telah memiliki pengetahuan dan berbagai cara untuk menjaga motivasi kerja karyawannya agar terus meningkat dan para karyawan yang ikut serta dalam pelaksanaan program motivasi berprestasi terus termotivasi.